Cover Image. Issue 4 (26th August 2021) - Wagaskar, Vinayak G.; Sobotka, Stanislaw; Ratnani, Parita; Young, James; Lantz, Anna; Parekh, Sneha; Falagario, Ugo Giovanni; Li, Li; Lewis, Sara; Haines, Kenneth; Punnen, Sanoj; Wiklund, Peter; et al.
Abstract: The cover image is based on the Original Article A 4K score/MRI based nomogram for predicting prostate cancer, clinically significant prostate cancer and unfavorable prostate cancer by Vinayak Wagaskar et al., https://doi.org/10.1002/cnr2.1357 . Abstract : The cover image is based on the Original Article A 4K score/MRI based nomogram for predicting prostate cancer, clinically significant prostate cancer and unfavorable prostate cancer by Vinayak Wagaskar et al., https://doi.org/10.1002/cnr2.1357 .